Characterization of the binding behavior, structure and foaming properties of bovine α-lactalbumin combined with saponin by the multi-spectroscopic and silico approaches. (March 2022) - Shi, Ruijie; Chen, Wei; Pan, Fei; Zhao, Panpan; He, Yanting; Yu, Rui; Fu, Runxiao; Munkh-Amgalan, Gantumur; Jiang, Zhanmei
Abstract: This work systematically researched the binding behavior mechanism and foaming properties of bovine α-lactalbumin (α-La) and glycyrrhizic acid (GA) or ginsenosides (GR) in bulk at pH 7.0 by using the methods of multi-spectroscopic, molecular docking and molecular dynamics (MD) simulation. The intrinsic fluorescence results showed that binding behavior mechanism of GA and GR bounded onto α-La was static quenching. Moreover, the Ka of α-La/GA (3.44 × 10 4 ) was larger than that of α-La/GR complex (9.57 × 10 2 ) at 298 K. The main driven forces of α-La/GA were hydrogen bonds, van der Waals and hydrophobic interaction forces, while only hydrophobic interaction force was involved in α-La/GR complex. Meanwhile, molecular docking result showed that the docking site of α-La/GA and α-La/GR was mainly located in sheet with S1, S2 or S3 and helix with H4 or h1. There were six hydrogen bonds in α-La/GA, whereas no hydrogen bond was present in α-La/GR. The MD results presented that the electrostatic interaction energy, the Van der Waals interaction energy and the nonpolar solvent energy were favorable for binding between α-La and GA or GR. Among them, the main contributed amino acid residues of α-La/GA complex were Thr33, Gln54, Tyr103, Trp104 and Leu110, while the main interacted residues of α-La/GR system were Trp60, Val99, Tyr103 and Trp104. Furthermore, GA and GR bonded onto α-La had insignificant impact on the secondary structure of α-La. Finally, the addition of GA and GR (1.0 mg/mL) induced a 155.57% and 111.11% increase in the foaming property of α-La. The obtained results provide some new insights to the interaction mechanism of α-La bounded with GA and GR. Additionally, it also indicates that α-La/saponin complex has the ability to apply in the protein-based foaming foods. Graphical abstract: Image 1 Highlights: The binding behavior mechanism of GA and GR bounded onto α-La was static quenching. The non-radiative energy transfer occurred in the α-La/GA and α-La/GR. The binding affinity of α-La/GA was larger than that of α-La/GR complex at 298 K. The foaming properties of α-La was increased in the presence of GA and GR.